Consumers' awareness and knowledge of nutritional labelling: a case study in Kuala Lumpur and Kota Kinabalu / Shalawati @ Salwa Ibrahim - Ibrahim, Shalawati @ Salwa (2008)
A total of 1200 questionnaires were distributed at supermarkets/hypermarkets in Kuala Lumpur and Kota Kinabalu. This study is carried out using the mall-intercept technique. These supermarkets/hypermarkets were selected randomly.- 608 (50.6%) was the return rate. The purpose of this study was: (1) to determine the demand and type of information consumers look for in nutritional labelling when making purchase decisions for food items, (2), to identify socio-demographic differences on the use of nutritional labelling, (3), to determine whether the use of labels is related to the dietary, health, religious or ethical needs of the consumers and (4) to determine the relationship between knowledge on nutrition and the use of nutritional labels. The socio-economic and demographic characteristics of the sample analyzed in this study are age, gender, ethnic group, marital status, and total household income, and academic qualification, field of expertise, location, special needs, and families with or without children at home. Female respondents represent half of the total respondents in this study. The findings suggest that respondents generally give priority to nutritional content related to general health when purchasing food .While the majority of age group is less than 30 years old with 327 respondents married, most of the respondents refer to nutritional labelling when making food purchases. Most of the respondents (71%) look at the nutrient content of the food when they read nutritional labelling. This suggests that respondents generally give priority to the nutritional content of foods that they are purchasing. The results show that reading of nutritional labelling on food packages is quite prevalent among Malaysian consumers in the urban areas where the sample is drawn. It is evident that the reading of nutritional labelling is influenced by awareness about the health aspects of food only in general term, rather than based on specific knowledge. This study revealed an interesting finding that Malaysian consumers in Kuala Lumpur and Kota Kinabalu take interest in reading nutritional labelling when making purchasing decisions. It is recommended that future research be undertaken to include all States in the country especially those States with less urban status.